2017
DOI: 10.1080/13697137.2017.1285879
|View full text |Cite
|
Sign up to set email alerts
|

Impact of risk-reducing salpingo-oophorectomy in premenopausal women

Abstract: The conclusions of this systematic review are limited by the absence of randomized, controlled trials. There is growing evidence from observational studies that RRSO may impact negatively on all-cause non-survival endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 70 publications
0
28
0
2
Order By: Relevance
“…PBSO renders an anticipated early menopause which has unfortunate physical and psychological consequences ([ 39 , 40 ]). Premenopausal women undergoing PBSO experience hot flashes and night sweats (40%), dyspareunia (17%), and decreased libido (22%) [ 41 ].…”
Section: Prophylactic Bilateral Salpingo-oophorectomy (Pbso)mentioning
confidence: 99%
“…PBSO renders an anticipated early menopause which has unfortunate physical and psychological consequences ([ 39 , 40 ]). Premenopausal women undergoing PBSO experience hot flashes and night sweats (40%), dyspareunia (17%), and decreased libido (22%) [ 41 ].…”
Section: Prophylactic Bilateral Salpingo-oophorectomy (Pbso)mentioning
confidence: 99%
“…However, the effect of hysterectomies and bilateral salpingo-oophorectomies on the sexual function of women has been a point of contention. Some studies have reported a positive effect of SM on psychological and sexual well-being and sexual performance [10,[29][30][31][32]. Conversely, Kokcu et al found that vaginal dryness increased in women with SM, but that SM did not have a more negative effect on female sexual performance than did NM [33].…”
Section: Clinical Researchmentioning
confidence: 97%
“…Bilateral oophorectomy in pre‐menopausal women — which, in conjunction with bilateral salpingectomy, may be used as a treatment for endometrial and ovarian cancer or may be recommended as a risk‐reduction treatment for pre‐menopausal women at high inherited risk of ovarian or breast cancer (eg, women with a BRCA1 or BRCA2 gene mutation) — induces surgical menopause 12 . Despite the lack of large prospective studies in cancer survivors, surgical menopause appears to cause more frequent and severe vasomotor and sexual symptoms than natural menopause 12 , 13 . Symptoms associated with surgical menopause as treatment for gynaecological cancer or to reduce the risk of breast cancer recurrence may, however, be difficult to distinguish from those associated with adjuvant treatments.…”
Section: Mechanisms Of Cancer‐related Menopausementioning
confidence: 99%
“…12 Despite the lack of large prospective studies in cancer survivors, surgical menopause appears to cause more frequent and severe vasomotor and sexual symptoms than natural menopause. 12,13 Symptoms associated with surgical menopause as treatment for gynaecological cancer or to reduce the risk of breast cancer recurrence may, however, be difficult to distinguish from those associated with adjuvant treatments.…”
Section: Surgical Menopausementioning
confidence: 99%